Industrial concentration, price-cost margins, and innovation - David Flath (Osaka University, Institute of Social and Economic Research (ISER), 2009)
This paper explores a panel data set matching establishment-based production statistics from Japan's Census of Manufacturers with wholesale price indices from the Bank of Japan, and Herfindahl indices from the Japan Fair Trade Commission. The data include annual observations over the period 1961-1990, for 74 industries at the 4-digit s.i.c. level. We estimate Cobb-Douglas production functions and Solow residuals for each industry and then use these estimates to further analyze the determinates of industrial concentration and innovation. The industries having great capital intensity, small employment of labor, and with high price-cost margins tend to be more concentrated. Cross-section estimates reveal a U-shaped mapping from concentration to innovation.
Keywords: L11; L13; L60; O30; 330